Intuitive interaction for exploring human anatomy in a VR setup - Michael-Grigoriou, Despina; Yiannakou, Panayiotis; Christofi, Maria (My University, 2017)
A vast majority of VR applications use interaction based on hand-held controllers. In this paper we present a novel application for exploring Human Anatomy which allows intuitive interaction based on eye gazing, gestures and physical hand movements. Experiments have been conducted to evaluate: (i) hand motion recognition technology for the feeling of immersion and intuitive interaction and (ii) the VR application in aspects of user experience and learning comparing to covey information through traditional digital representation methods. Preliminary results demonstrate an advantage of the VR application and hand motion recognition in a number of aspects investigated.
Keywords: Digital representations; Hand motion; Hand movement; Human anatomy; Intuitive interaction; Novel applications; User experience; VR applications